The impact of STEAM education on learners’ cognitive development: an analysis of global practices - Zhelezniakova, Natalia; Aleksandrova, Tetiana; Vizir, Maryna (Інститут обдарованої дитини НАПН України, 2026)
The development and training of learners directly influence the future of science, the economy, and the country’s sustainable educational progress. The engagement of learners in STEAM practices, which integrate science, technology, engineering, arts, and mathematics, plays a crucial role in developing key competencies of the modern world, including communication skills, the ability to collaborate, innovative thinking, and critical analysis. The STEAM approach enhances students’ interest in learning by transforming theoretical knowledge into practice-oriented activities and research-based experiences. It also fosters adaptability to the rapid technological changes of the modern world. In Ukraine, this educational approach is gaining increasing momentum and is being integrated even at the level of primary education. In our study, leading international STEAM education practices were analyzed, and key conclusions regarding current research issues in this field were summarized.
Keywords: STEAM education; educational progress; innovative thinking; critical analysis; international experience; 2026а